Clinical Effect of Modified Ultrasound-Guided Subclavian Vein Puncture - Yun-Shui Zhang; Shuang-Long Zhang; Wen-Min Guo; Tao Liu; Yu-Jie Ma (International Journal of Clinical Practice)
Objective. This study compared the effect of ultrasound-guided subclavian vein puncture with traditional blind puncture and the double-screen control method by evaluating the one-time puncture success and total success rates, the completion time for puncture and catheterization, and short-term complications. Methods. From January 2020 to January 2021, 72 patients with right subclavian venipuncture catheterization were collected, 12 of whom were excluded (including 3 cases of pneumothorax, 2 cases of hemothorax, 1 case of difficult positioning of thoracic deformity, 1 case of severe drug eruption, 3 cases of clavicle fracture, and 1 case of severe coagulation dysfunction). The remaining 60 cases were randomly divided into the traditional group (n = 30) and the improved group (n = 30). We record two sets of ultrasound localization time, puncture time, one-time puncture power, total puncture success rate, and short-term (24-hour) complications. Results. Compared with the traditional group, the ultrasound positioning time and puncture time in the improved group were significantly reduced and the puncture success rate was higher. There were no complications, such as incorrect arterial puncture and the occurrence of pneumothorax, in either group. Conclusion. The improved ultrasound-guided subclavian vein catheterization technique can greatly reduce the catheterization time and improve the success rate of puncture and catheterization. It can also reduce the occurrence of complications and damage to adjacent tissues. The operation is simple, fast, and easy to master, and it has a high popularization clinical value.